The common solutions of complementarity problems and a zero point of maximal monotone operators by using the hybrid projection method - Promluang K. (2017)
© 2016, North Atlantic University Union. All rights reserved. In this paper, we propose a projection method for solving nonlinear complementarity problems and a zero point of maximal monotone operators. Strong convergence theorems are established for solving the common solutions of complementarity problems and a zero point of maximal monotone operators together with a system of generalized equilibrium, variational inequality and fixed point problems in a uniformly smooth and 2-uniformly convex real Banach space. Moreover, we also apply the result to Hilbert spaces.